Distal femur fractures: management and outcomes by a modified anterolateral swashbuckler approach - Ghirardelli, Stefano; Touloupakis, Georgios; Theodorakis, Emmanouil; Antonini, Guido; Violante, Bruno; Indelli, Pier Francesco (Acta Biomedica Atenei Parmensis, 2024)
Background: The treatment of distal femur fractures represents a challenging task. General and local factors, including bone quality, articular surface involvement, fracture comminution, associated soft tissue injuries and ultimately fixation system, all play a role in the final clinical outcome. Current surgical approaches often undermine patellar vascularization and integrity of the extensor apparatus, not guaranteeing sufficient visualization of the medial condyle. This technical note presents the efficacy and safety a new surgical technique to address distal femoral fractures.Methods: The original "swashbuckler" surgical approach was modified in order to obtain a better visualization of the lateral and medial femoral condyles without affecting the knee extensor mechanism and the anastomotic arterial supply of the patella. This modified surgical approach was utilized in a consecutive series of patients presenting with an AO Foundation/Orthopaedic Trauma Association (AO/OTA) 33 distal femur or periprosthetic fracture of the knee. The final outcome was recorded according to a functional evaluation scoring system.Results: Twelve patients (2 males and 10 females) with a mean age of 67,8 years were included in this series. The same, modified "swashbuckler" surgical approach was applied in all cases. Multiple internal fixation techniques, including a single lateral plate, a combination of a lateral and medial plate, a single lateral plate associated with lag screws, were used to obtain a satisfactory stabilization of the fracture site. All patients were reviewed at a minimum one-year follow up (median 15 months): all patients regained their level of activities of daily living. No major intraoperative or postoperative complications were recorded.Conclusions: The modified swashbuckler approach allows anatomical reduction and appropriate fixation without sacrificing the blood supply to the patella and ensures rapid weight bearing resumption thanks to an intact extensor mechanism.